Closure of wide patent ductus arteriosus using a fenestrated muscular VSD occluder device in a pediatric patient with Down syndrome and pulmonary hypertension - Osman Güvenç; Murat Saygı; İbrahim Halil Demir; Ender Ödemiş (KARE Publishing, 2017)
Patients with wide patent ductus arteriosus and significant pulmonary hypertension not treated in time constitute a significant problem for cardiologists. For these patients, tests that could aid in decision-making for further planning include reversibility and balloon occlusion tests performed in the catheterization laboratory. Devices developed for the closure of ductus as well as different devices with off-label use may be employed in patients scheduled for transcatheter occlusion. When result of reversibility test is borderline positive, the use of fenestrated device may be applicable for selected patients. Presently described is case of a 10-year-old patient with Down syndrome who had a wide ductus and systemic pulmonary hypertension. Transcatheter closure procedure was performed with off-label use of a fenestrated muscular ventricular septal defect occluder device.